Regional touristic cluster as one of the factors of touristic development on the border territories of Kazakhstan and Russia - Temirbulatova, M.A.; Agybetova, R.Y.; Yerzhanova, S.K.; Omarova, A.S.; Mioara, B. (BUKETOV BUSINESS REVIEW, 2019)
The article is devoted to the problems of forming regional tourist clusters in the border areas of Kazakhstan and Russia, as well as methodologies for their creation and further development. The global tourism industry has significantly globalized and, with its rapid dynamics of development, has become a contender for the leading global industry. International tourism is currently one of the most dynamically developing branches of foreign economic activity. Tourism, both in Russia and in Kazakhstan, is recognized as one of the main priorities of the country’s development, contributing to the diversification of the economy in the nonextractive sector. As one of the largest and fastest growing industries in the world, tourism has an impact on related industries like telecommunications and transport, construction and trade, and agriculture, contributing to the socio-economic development of regions. Kazakhstan, having a rich recreational potential, is characterized by a relatively weak level of tourism development, as evidenced by its insufficient share in the country’s GDP. Socio-economic transformations observed in many CIS countries, their openness of border regions under the influence of integration processes in the world community, contribute to the strengthening of tourist mobility between neighboring countries. In the modern scientific community, recently, problems of the development of border regions of adjacent states and the prospects and directions for the development of crossborder cooperation are widely discussed. The usage of the «cluster-activate public strategy (CAPS)» as a network organization of economic interaction, adapted to any changes in the internal and external environment with the optimal distribution of growth coordinators, the conjugation of intellectual capital with the requirements of scientific and technological progress, is able to provide innovative breakthrough of the territory’s economy, satisfactory resolution of the main tasks of any production process and ensuring its sustainability and reproduction. A model of Kazakhstan-Russian tourist cluster was presented in the context of four organizational levels of research of regional tourist destinations, as well as the main directions for the creation and development of tourist clusters in the border areas of Kazakhstan and Russia.